The Analysis of Kinesics Used by English Teacher in ELT Classroom - Ilen Malnab; Isna Humaerah (AL LUGHAWIYAAT, 2020)
In frame of qualitative research, this study is aimed to analyze the kinds of teacher’s nonverbal communication used in ELT classroom which delimited on kinesics. The participant is one lecturer in South Sulawesi (Indonesia). Data is collected through observation and video recording and analyzed by using Ekman's (1969) nonverbal communication theory. The result of the research show that the teacher used nonverbal communication type kinesics such as using emblem, illustrators, effect display, regulators, and adaptors. Nonverbal communication type of kinesics that most frequently used by the teacher is illustrators, regulators, and emblems. In conclusion, the teacher used all of kind’s nonverbal communication on kinesics and applied them in teaching and learning process.